Analysis of An Indonesian E-Commerce Website: Gap Between Actual Performance and Users' Expectation - Pradana, Mahir; Ichsan, Muhammad (Forum Manajemen Indonesia (FMI), 2018)
For an e-commerce company, a reliable website is a basic requirement in the expansion of its business. This study aimed to describe the level of quality that is perceived by customers of an e-commerce website in Indonesia, based on the judgment of the actual quality and perceived quality developed from Website Quality (WebQual) theory. This research employs WebQual dimensions namely usability, information quality, and service interaction to be further analyzed by using Gap Analysis method. The research was done by spreading questionnaires to 100 respondents in Bandung, Indonesia, to determine what are the factors determining website quality of Shopee Indonesia. The result shows that overall there are value gaps between the actual quality (performance) and ideal quality (importance) of the website.   Keywords: E-Commerce; Website Quality; Information Technology; Online business